Topical Sirolimus 0.2% Gel for the Management of Tuberous Sclerosis Complex-Related Cutaneous Manifestations: An Interim Analysis of Postmarketing Surveillance in Japan - Akemi Egami; Shinji Takahashi; Takeshi Kokubo; Sreedevi Boggarapu; Eric Beresford (Adis, Springer Healthcare, 2023)
Abstract Introduction Tuberous sclerosis complex (TSC) is a rare autosomal dominant genetic disorder affecting several organs, including skin. We sought to assess the real-world effectiveness and safety of a topical sirolimus 0.2% gel treatment for TSC-related cutaneous manifestations. Methods We conducted an interim analysis of postmarketing surveillance conducted in Japan over 52 weeks. A total of 635 and 630 patients were included in the safety and efficacy analysis sets, respectively. Improvement rate of overall cutaneous manifestations, responder rate of improvement in individual lesions, adverse events (AEs), adverse drug reactions (ADRs), and patient satisfaction level of topical sirolimus 0.2% gel treatment were evaluated along with patient characteristics associated with the improvement rate of cutaneous manifestations or safety. Results The mean age of the patients was 22.9 years and 46.1% were men. At week 52 of treatment, the overall improvement rate was 74.8% and the responder rate was the highest for facial angiofibroma (86.2%). Overall, the incidence rates of AEs and ADRs were 24.6% and 18.4%, respectively. Efficacy was associated with age (< 15, ≥ 15 to < 65, and ≥ 65 years, p = 0.010), duration of use (p < 0.001), and total dosage (p = 0.005). Safety was associated with age (< 15, ≥ 15 to < 65, and ≥ 65 years, p = 0.011) and duration of use (p < 0.001). However, when the broad age group (≥ 15 to < 65) was subcategorized by 10-year intervals, the incidence of ADRs was similar among the age groups with no significant differences. Hepatic or renal impairment or concomitant use of systemic mTOR inhibitors had no effect on the effectiveness or safety. Overall, 53% of patients were "very satisfied" or "satisfied" with the treatment received. Conclusions Topical sirolimus 0.2% gel is effective in the management of TSC-related cutaneous manifestations and generally well tolerated. Age and duration of usage had a significant association with the effectiveness or safety of topical sirolimus 0.2% gel, whereas total dosage had a significant association with the effectiveness.